Bioengineered Anthocyanin-Enriched Tomatoes: A Novel Approach to Colorectal Cancer Prevention - Md Suzauddula; Kaori Kobayashi; Sunghun Park; Xiuzhi Susan Sun; Weiqun Wang (Foods)
Colorectal cancer (CRC) remains a significant global health challenge, with barriers to effective prevention and treatment including tumor recurrence, chemoresistance, and limited overall survival rates. Anthocyanins, known for their strong anti-cancer properties, have shown promise in preventing and suppressing various cancers, including CRC. However, natural sources of anthocyanins often fail to provide sufficient quantities needed for therapeutic effects. Bioengineered crops, particularly anthocyanin-enriched tomatoes, offer a viable solution to enhance anthocyanin content. Given its large-scale production and consumption, tomatoes present an ideal target for bioengineering efforts aimed at increasing dietary anthocyanin intake. This review provides an overview of anthocyanins and their health benefits, elucidating the mechanisms by which anthocyanins modulate the transcription factors involved in CRC development. It also examines case studies demonstrating the successful bioengineering of tomatoes to boost anthocyanin levels. Furthermore, the review discusses the effects of anthocyanin extracts from bioengineered tomatoes on CRC prevention, highlighting their role in altering metabolic pathways and reducing tumor-related inflammation. Finally, this review addresses the challenges associated with bioengineering tomatoes and proposes future research directions to optimize anthocyanin enrichment in tomatoes.